Exploring sexual harassment and related attitudes in Beninese high schools: a field study - Waubert de Puiseau, Berenike; Roessel, Janin (Psychology, crime & law, 2013)
Sexual harassment severely impacts the educational system in the West African country Benin and the progress of women in this society that is characterized by great gender inequality. Knowledge of the belief systems rooting in the sociocultural context is crucial to the understanding of sexual harassment. However, no study has yet investigated how sexual harassment is related to fundamental beliefs in Benin or West African countries. We conducted a field study on 265 female and male students from several high schools in Benin to investigate the link between sexual harassment and measures of ambivalent sexism, gender identity, and rape myth acceptance. Almost half of the sample reported having experienced sexual harassment personally or among peers. Levels of sexism and rape myth acceptance were very high compared to other studies. These attitudes appeared to converge in a sexist belief system that was linked to personal experiences, the perceived probability of experiencing and fear of sexual harassment. Results suggest that sexual harassment is a societal problem and that interventions need to address fundamental attitudes held in societies low in gender equality.